2022
DOI: 10.3390/agronomy12092056
|View full text |Cite
|
Sign up to set email alerts
|

Decisive Climatic Factors for Production of Bioactive Saponarin-Rich Barley Sprouts: A Study of Seasonal Effect

Abstract: Saponarin content in barley sprouts may vary greatly with environmental conditions, such as climate, leading to difficulty in uniformly producing saponarin-rich barley sprouts in situ farmlands throughout the year. This research was an early attempt to identify the optimal conditions of various climatic factors, such as temperature, light, and humidity according to seasonal change, for maximizing the saponarin content of sprouted barley through the two-year field experiment. As a result, the growth index, as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Barley ( Hordeum vulgare L.) belongs to the family Poaceae (Graminaea), and is one of the leading global staple crops due to its wide range of nutrition and medicinal uses. , Although barley has been used as a food grain since the ancient times, until recently, the nutritional value of young barley leaves (YBL) was overlooked despite harboring significant metabolites, such as vitamins, minerals, chlorophyll, and flavone glycosides. , The green YBL also accumulates abundant saponarin (SA), which is a unique flavone with both C - and O -glycosides (apigenin-6- C -glucosyl-7- O -glucoside or isovitexin-7- O -glucoside) (Figure ). The genetic variation of SA in plants and its biological implications have led to industrial demand for its extraction from YBL in Korea, Japan, and other parts of world. , However, the level of a single SA compound in YBL can greatly vary with environmental conditions and growth stages. Numerous previous studies have shown the significant capacity of SA to counter the effects of severe environmental stresses, such as drought, heat, and erratic temperature fluctuation. Additionally, exposure to ultraviolet (UV) and light-emitting diode (LED) radiations resulted in elevated SA production in YBL, which was accompanied by increased and steady transcript levels of the corresponding SA biosynthetic genes. Moreover, the application of nonthermal plasma and mechanical stresses, as well as elevated carbon dioxide (eCO 2 ) have been reported to upregulate the SA level and enhance its antioxidant activity. …”
Section: Introductionmentioning
confidence: 99%
“…Barley ( Hordeum vulgare L.) belongs to the family Poaceae (Graminaea), and is one of the leading global staple crops due to its wide range of nutrition and medicinal uses. , Although barley has been used as a food grain since the ancient times, until recently, the nutritional value of young barley leaves (YBL) was overlooked despite harboring significant metabolites, such as vitamins, minerals, chlorophyll, and flavone glycosides. , The green YBL also accumulates abundant saponarin (SA), which is a unique flavone with both C - and O -glycosides (apigenin-6- C -glucosyl-7- O -glucoside or isovitexin-7- O -glucoside) (Figure ). The genetic variation of SA in plants and its biological implications have led to industrial demand for its extraction from YBL in Korea, Japan, and other parts of world. , However, the level of a single SA compound in YBL can greatly vary with environmental conditions and growth stages. Numerous previous studies have shown the significant capacity of SA to counter the effects of severe environmental stresses, such as drought, heat, and erratic temperature fluctuation. Additionally, exposure to ultraviolet (UV) and light-emitting diode (LED) radiations resulted in elevated SA production in YBL, which was accompanied by increased and steady transcript levels of the corresponding SA biosynthetic genes. Moreover, the application of nonthermal plasma and mechanical stresses, as well as elevated carbon dioxide (eCO 2 ) have been reported to upregulate the SA level and enhance its antioxidant activity. …”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the insufficiency of the light intensity (i.e., 200 μmol m –2 s –1 ) experienced by these barley sprouts; this should be compared to the previously determined saturation point for barley plant photosynthesis of approximately 400 μmol m –2 s –1 PPFD . Similarly, several studies have reported that barley sprouts grown at low light intensity (i.e., 380 μmol m –2 s –1 ) using a chamber system contained low saponarin content (i.e., from 20 to 80 mg 100 g –1 ). ,, However, under higher light intensities (i.e., 570–1,700 μmol m –2 s –1 ) recorded in outdoor fields, saponarin content of barley sprouts ranged from 1000 to 1900 mg 100 g –1 . Moreover, the authors of previous study observed a positive correlation between saponarin yield and light duration ( r = 0.446, p = 0.006) but not light intensity ( r = 0.095, p = 0.584) .…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, several studies have reported that barley sprouts grown at low light intensity (i.e., 380 μmol m –2 s –1 ) using a chamber system contained low saponarin content (i.e., from 20 to 80 mg 100 g –1 ). ,, However, under higher light intensities (i.e., 570–1,700 μmol m –2 s –1 ) recorded in outdoor fields, saponarin content of barley sprouts ranged from 1000 to 1900 mg 100 g –1 . Moreover, the authors of previous study observed a positive correlation between saponarin yield and light duration ( r = 0.446, p = 0.006) but not light intensity ( r = 0.095, p = 0.584) . Conversely, in this study, saponarin content in barley sprouts showed a significant polynomial relationship with Cum.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations